Lasiopteridi (Diptera: Cecidomyiidae) with aciculate ovipositor and larval puparium - Harris, Keith M. (Zootaxa, 2008)
The Acer seed midge, a new species and genus of gall midge, Acumyia acericola (Diptera: Cecidomyiidae), is described on the basis of larval, pupal and adult specimens from collections made at Hainault Forest and Lambourne Common, Essex, and other parts of the UK, during 2006–08. The new genus is distinguished from all known genera of Cecidomyiidae by the combination of a larval puparium and an aciculate ovipositor. It is assigned to the supertribe Lasiopteridi and probably belongs in the tribe Dasineurini. Larvae develop in the ovular cavities of field maple, Acer campestre L., and Norway maple, A. platanoides L., and prevent seed development. Observations suggest that this species is biennial, with final instar larvae surviving for at least two years in Acer seeds lying in leaf litter and soil. The species has been recorded from Acer seeds in continental Europe and plant quarantine interceptions in the USA indicate that the same or similar species are present in Japan and China. Two puparia, possibly of this species, were discovered recently in A. palmatum fruits collected in Honshu, northern Japan.